Heliopolis , Ägypten: Undulierende Umfassungsmauern der ägyptischen Spätzeit - Beiersdorf, Max Johann (e-Forschungsberichte des DAI, 2023)
The area of the Temple of Heliopolis in Matariya was enclosed by two parallel courses of mud brick walls of different date, measuring about 1100 m east-west and 900 m north-south. Approximately 100 m of this outer enclosure wall are rather well preserved to a height of 3 m. The architectural survey finished the documentation of 60 m and pursued a section on top of the outer enclosure wall to investigate the junction of two segments. Built in alternate panels of concave and convex courses of mud brick, the structural analysis of the walls allows to assume, that the stability could be increased in conditions of permanent weight. Based on these observations it can be concluded that this construction technique brought essential structural benefits.